Encouraging Landscape Water-Conservation Behaviors #3: Developing Extension and Outreach Messages That Encourage Landscape Water Conservation Practice Adoption - Courtney Owens; Laura A. Warner; Joy Rumble; Alexa Lamm; Randall Cantrell (EDIS, 2015)
Message framing can be an effective tool for crafting messages for a target audience. This 5-page fact sheet explains how Extension can use gain and loss message framing to encourage Florida residents who irrigate their home landscape to adopt water-conservation practices. Part three of the series Encouraging Landscape Water-Conservation Behaviors and written by Courtney Owens, Laura Warner, Joy Rumble, Alexa Lamm, and Randall Cantrell, and published by the UF Department of Agricultural Education and Communication, June 2015.